Efficacy of immune checkpoint inhibitors plus molecular targeted agents after the progression of lenvatinib for advanced hepatocellular carcinoma - Xie, Fucun; Chen, Bowen; Yang, Xu; Wang, Huaiyuan; Zhang, Ge; Wang, Yanyu; Wang, Yunchao; Zhang, Nan; Xue, Jingnan; Long, Junyu; Li, Yiran; Sun, Huishan; et al. (Frontiers in Immunology, 2022)
Abstract Background: Lenvatinib is a standard first-line systemic therapy in advanced hepatocellular carcinoma (aHCC) and is widely used in all lines. However, the efficacy and safety of immune checkpoint inhibitors (ICIs) plus molecular targeted agents (MTAs) after the progression of lenvatinib treatment are unclear. Objective: The aim of this study was to evaluate the anticancer effects of ICI plus MTA in patients with aHCC who progressed after lenvatinib. Methods: We retrospectively included aHCC patients treated with ICI plus MTA after the progression of lenvatinib from two medical centers. Participants who continued lenvatinib treatment were classified into the “ICI+Lenva” group, while the “ICI+Others” group included patients receiving other MTAs. The efficacy endpoints were progression-free survival (PFS), post-progression survival (PPS), overall survival (OS), and tumor response following RECIST v1.1. Safety was evaluated according to Common Terminology Criteria for Adverse Events v5.0. Results: In this study, 85 eligible aHCC patients were enrolled, including 58 in the ICI+Lenva group and 27 in the ICI+Others group. At a median follow-up time of 22.8 months, the median PPS and PFS were 14.0 (95% CI: 9.0-18.2) and 4.5 months (95% CI: 3.5-8.3), respectively. The objective response and disease control rates were 10.6% and 52.9%, respectively. No significant differences were observed in any of the efficacy endpoints between the two groups. Prolonged OS was associated with Child‒Pugh grade A, AFP < 400 IU/ml, and concomitant locoregional treatment. All patients experienced adverse events (AEs), but no fatal AEs were observed. Conclusion: ICI plus MTA in HCC patients after the progression of lenvatinib presented high antitumor activity and safety. Patients could continue lenvatinib treatment and receive ICIs as well as locoregional treatment to achieve better OS.